Relationship Between Knowledge And Attitude Of Mothers Who Have Toddlers About Giving Vitamin A Capsules In The Pustu Bandarlama Area In 2020 - Siti Nurmawan Sinaga (Institute of Computer Science (IOCS), 2020)
Toddlerhood is a period where the process of growth and development is most important in children. At this time toddlers need vitamin A in sufficient quantities for growth and endurance of the body against disease. Children under five are the target of the fourth millennium development in Indonesia, bearing in mind that at this stage of age, they are very vulnerable to health problems, especially the problem of vitamin A deficiency in 2020. This type of research uses observational analytic research methods with a cross-sectional approach. The subjects of this study were mothers who had children under five in the Pustu Bandarlama Region with a total of 39 respondents. Retrieval of data by questionnaire knowledge of mothers and attitudes of mothers who have toddlers about the provision of vitamin A capsules. The analysis was carried out univariately and bivariately. The formula in this study uses the Chi Square formula. Knowledge and attitudes of mothers who have children under five years old are associated with the provision of vitamin A capsules with ap value = 0.000. The results showed that there was a relationship between knowledge and attitudes of mothers who had children under five about giving vitamin A capsules. There is a relationship between the knowledge of mothers who have toddlers about the provision of vitamin A capsules. There is a relationship between the attitudes of mothers who have toddlers about giving vitamin A capsules. It is recommended that the health workers in the Pustu Bandarlama be expected to improve the level of public knowledge, especially mothers who have children under five through counseling about the benefits of providing vitamin A to toddlers. Mothers are expected to care about things that are very important for toddlers. Don't just focus on toddler food and drinks but also support baby needs such as vitamin A.